Inhaled Polymyxin in Treatment of Elderly Patients with Severe Community-Acquired Klebsiella pneumoniae-Induced Pneumonia - V. I. Sakharov; P. I. Mironov; I. A. Ruslykova; I. I. Lutfarakhmanov (Креативная хирургия и онкология, 2020)
Background. Inhaled administration of antibacterial drugs (ABD) is a new insufficiently studied area of modern pulmonology. Its feasible advantages comprise a targeted drug delivery to the infection site, amplified antibiotic concentration in tracheobronchial secretion and reduced systemic toxicity risks. The most common inhaled ABDs include aminoglycosides and polymyxinE (colistin).Aim. A comparison of patient cohorts with severe communityacquired pneumonia induced by Klebsiella pneumoniae receiving and not receiving inhaled colistin.Materials and methods. The study conducted is a retrospective multicentre controlled nonrandomised assay. Among the 45 patients included, 20 were and 25 were not receiving colistin inhalation. The endpoint was survival. Data were analysed with Statistica 6.0.Results and discussion. The cohorts differed significantly neither in the main clinical and laboratory values, nor in point scoring of severity and outcome. However, statistical significance was obtained for differences in the ALV (p = 0.04) and pneumonia resolution (p = 0.044) times.Conclusion. Inhaled polymyxinsupplemented therapy for severe communityacquired pneumonia induced by Kl. pneumoniae significantly reduces the ALV and pneumonia resolution times in elderly and senile patients but does not affect survival.